Bimbingan Teknis Pembuatan dan Penulisan Inovasi Pelayanan Publik Bidang Pendidikan Tahun 2021 - Yohanes Susanto; R.A. Zubaidah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
The purpose of this study is to explain the performance of junior high school teachers in the city of palembang, the innovation revolution in the development of public services in schools. This study used a quantitative approach and descriptive data as well as quantitative data by using several questions or questionnaires to respondents or technical guidance participants. Quantitative data was obtained through questionnaires with intervals. The results showed that the participants of the technical guidance of public service innovations were very good, it was proven that there was an increase in the value of the results of the t test, pre-test scores and t-test scores post = test, there was an increase of 37.64%, this indicates a fairly good absorption of guidance participants technical. This assessment becomes a reference in implementing teachers in an effort to improve public service innovation in schools. It is recommended to the organizers of the education office of Palembang City in the future that there is a need for technical training on strategic management of teacher innovation in utilizing the potential of the school environment they have for the development of knowledge and skills of their students.